2017
DOI: 10.1002/ep.12623
|View full text |Cite
|
Sign up to set email alerts
|

Composite of biomass and lead resistent Aspergillus oryzae for highly efficient aqueous phase Pb(II) adsorption

Abstract: In this research, compound biosorbent peanut shell‐HA (PSH) and millet chaff‐HA (MCH), which were composited by peanut shell (PS) and millet chaff (MC) with lead resistent Aspergillus oryzae (HA), respectively, were used to remove Pb2+ from aqueous solution. The characterize of biosorbents were analyzed by FTIR and SEM. Batch experiments were performed to evaluate the effect of pH, biosorbent concentration, initial Pb2+ concentration and contact time on the Pb2+ removal. The results indicated that the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…This scenario typically occurs during the start of the adsorption. The PFO Pb(II) adsorption rate for Aspergillus is expected to range from 0.0190 to 0.1676 [27]. The analytical form of the PFO can be seen in Equation (5).…”
Section: Pseudo-first-order (Pfo) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This scenario typically occurs during the start of the adsorption. The PFO Pb(II) adsorption rate for Aspergillus is expected to range from 0.0190 to 0.1676 [27]. The analytical form of the PFO can be seen in Equation (5).…”
Section: Pseudo-first-order (Pfo) Modelmentioning
confidence: 99%
“…When the adsorbate concentration is low enough the Langmuir kinetic model can be simplified to a PSO model. The PSO Pb(II) adsorption rate for Aspergillus is expected to range from 0.0019 to 0.0200 [27]. The analytical form of the PSO model can be seen in Equation ( 7):…”
Section: Pseudo-second-order (Pso) Modelmentioning
confidence: 99%
“…Ag/ACF composites increased 2.4~4.2 (tb) times and 1.3 times compared to ACF, indicating that the adsorption performance of AA by Ag p was improved at breakthrough and exhaustion time. In addition, the height of t transfer zone was also reduced by 17 to 31% in Ag/ACF composites compared suggesting that the fixed bed column due to low mass transfer resistance can be us efficiently [30]. It was found that Ag particles precipitated on the surface of the the LPP reaction improved the AA adsorption ability, and the amount of Ag p acted as a major influence factor on the adsorption performance improvement presumed to be due to the high adsorption affinity between the Ag particles on t surface and the carbonyl group of AA [31,32].…”
Section: Resultsmentioning
confidence: 95%
“…In addition, utilization of the traditional fixed-bed reactor (single-column mode) for water defluoridation is still hindered by its relatively weak adsorption affinity. On the one hand, the relatively weak adsorption affinity resulted in a long mass transfer zone, , and thus considerable amounts of adsorbents were far from reaching adsorption equilibrium when fluoride in the effluent exceeded the MCL value ( e.g ., 1.0 mg/L) . On the other hand, fluoride concentration in the effluent might rise steadily, increasing the requirement for water quality monitoring to avoid excessive contaminants.…”
Section: Introductionmentioning
confidence: 99%